Fever After Traumatic Spinal Cord Injury: A Case of Brucella Sepsis. Issue 11 (16th November 2013) - McCormick, Zack; Lynch, Meaghan; Chen, David
Abstract : Fever during acute rehabilitation in patients with a spinal cord injury is a common problem. Infection, typically of the urinary or respiratory tract, is the most frequent cause of fever in these circumstances. We report a case of Brucella sepsis as a cause of fever in a patient with a spinal cord injury who was undergoing acute rehabilitation. We discuss the epidemiology, differential diagnosis, and evaluation of fever in persons with Brucella infection, as well as fever in patients with a spinal cord injury in the acute rehabilitation setting.